2021
DOI: 10.1186/s10020-021-00339-7
|View full text |Cite
|
Sign up to set email alerts
|

ets1 associates with KMT5A to participate in high glucose-mediated EndMT via upregulation of PFN2 expression in diabetic nephropathy

Abstract: Background Diabetic nephropathy (DN) is currently the leading cause of end-stage renal disease globally. The endothelial-to-mesenchymal transition (EndMT) of glomerular endothelial cells has been reported to play a crucial role in DN. As a specific form of epithelial-to-mesenchymal transition, EndMT and epithelial-to-mesenchymal transition may exhibit mutual modulators. Profilin 2 (PFN2) has been reported to participate in epithelial-to-mesenchymal transition. Moreover, ETS proto-oncogene 1 (et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“… 34 Furthermore, binding of lysine methyltransferase 5A to the transcription factor ETS proto‐oncogene 1 enhanced profilin 2 transcriptional activity and promoted hyperglycaemia‐induced EndMT in glomerular ECs of DKD patients and rats. 35 These evidence supports the involvement of EndMT in the development of renal fibrosis in patients with DKD.…”
Section: Endmt and Dkdsupporting
confidence: 64%
“… 34 Furthermore, binding of lysine methyltransferase 5A to the transcription factor ETS proto‐oncogene 1 enhanced profilin 2 transcriptional activity and promoted hyperglycaemia‐induced EndMT in glomerular ECs of DKD patients and rats. 35 These evidence supports the involvement of EndMT in the development of renal fibrosis in patients with DKD.…”
Section: Endmt and Dkdsupporting
confidence: 64%
“…Epigenetics play a crucial role in hyperglycemic vascular endothelial injury. Moreover, our previous studies illustrated that SETD8 participates in the pathogenesis of DN [ 19 ]. IHC assay indicated that SETD8 was downregulated in glomeruli of DN participants and rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 , 17 ]. Our previous study revealed that suppression of SETD8 participates in high-glucose-mediated vascular endothelial injury, thus mediating the development of diabetic nephropathy [ 18 , 19 ]. SETD8 may thus possibly become a potential therapeutic target in diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ETS1 is a mediator that promotes kidney inflammation and fibrosis [ 47 ] and leads to kidney injury by damaging cell endothelium [ 48 ]. ETS1 plays an important role in diabetic nephropathy and hypertensive nephropathy-related renal damage.…”
Section: Discussionmentioning
confidence: 99%